The nesting place : it doesn't have to be perfect to be beautiful - Smith, Myquillyn (Zondervan, 2014)
"Drawing on her years of experience creating beauty in her 13 different homes, Myquillyn will show you how to think differently about the true purpose of your home and simply and creatively tailor it to reflect you and your unique style--without breaking the bank or stressing over comparisons"--Amazon.com.